The Effects of Role-Play on Students’ Speaking Confidence in Asking and Giving Opinions - Tiara Kirani; Dwi Agustina (Journal of English Language and Education, 2026)
Speaking confidence is a vital aspect in English learning because it affects students’ willingness to participate actively in classroom interaction. However, many junior high school students still experience anxiety and hesitation when speaking English, particularly in asking and giving opinions. Role-play is considered beneficial because it provides meaningful and supportive opportunities for students to practice communication and express ideas with less fear of making mistakes. This current study aimed at revealing how the role-playing approach affected students' confidence in speaking. Employing a pre-experimental study, the writers involved the eighth-grade students from SMP Islam Simbang Wetan Pekalongan, Central Java, Indonesia. Data were collected through a role-play-based speaking test using an analytic speaking rubric. The findings revealed a statistically significant increase in students' speaking confidence in asking and offering opinions, with the mean score rising from 57.26 to 70.83. The study concluded that role-play effectively improved students’ speaking confidence and encouraged active participation in English speaking activities.